Efficacy of Tasimelteon (HETLIOZ®) in the Treatment of Jet Lag Disorder Evaluated in an 8-h Phase Advance Model; a Multicenter, Randomized, Double-Blind, Placebo-Controlled Trial - Polymeropoulos, Christos M.; Mohrman, Michael A.; Keefe, Madison S.; Brzezynski, Jennifer L.; Wang, Jingyuan; Prokosch, Lydia S.; Polymeropoulos, Vasilios M.; Xiao, Changfu; Birznieks, Gunther; Polymeropoulos, Mihael H. (Frontiers in Neurology, 2020)
Background: Most travelers experience Jet Lag Disorder (JLD) symptoms due to misalignment of their circadian rhythms with respect to the new time zone. We assessed the efficacy and safety of tasimelteon (HETLIOZ®) in healthy participants using a laboratory model of JLD induced by an 8-h phase advance of the sleep-wake cycle (JET8 Study). We hypothesized that tasimelteon treatment in participants experiencing JLD would cause increased sleep time, increased next-day alertness, and reduced next-day sleepiness. Methods: We undertook a randomized, double-blind, placebo-controlled trial in 12 US clinical research sleep centers. We screened healthy adults ages 18-73 years, who were eligible for the randomization phase of JET8 if they typically went to bed between 21:00 and 01:00, slept between 7-9 hours each night, and slept at a consistent bedtime. We used block randomization stratified by site to assign participants (1:1) to receive a single oral dose of tasimelteon (20mg) or placebo 30 min before their 8-h phase-advanced bedtime. The primary endpoint was Total Sleep Time in the first 2/3 of the night (TST2/3), which was measured by polysomnography during the 8-h sleep episode, and assessed in the intent-to-treat population. The trial is completed and registered with ClinicalTrials.gov, NCT03373201. Results: Between October 16, 2017 and January 17, 2018, we screened 607 healthy participants for JET8, of whom 320 (53%) were assigned to receive tasimelteon (n=160) or placebo (n=160). Tasimelteon treatment increased TST2/3 (primary endpoint) by 60.3 min (95%CI 44.0 to 76.7, P<0.0001) and whole night TST by 85.5 min (95% CI 64.3 to 106.6, P<0.0001), improved next day alertness, next day sleepiness, and shortened latency to persistent sleep by -15.1 min (95% CI -26.2 to -4.0, P=0.0081). Conclusion: A single dose of tasimelteon improves the primary symptoms of JLD, including nighttime insomnia and next day functioning among participants in a laboratory model of JLD simulating eastward trans-meridian travel by inducing an 8-hour phase advance of the sleep-wake cycle.